PERAN KEPALA SEKOLAH SEBAGAI LEADER (PEMIMIN) DI SEKOLAH MENENGAH ATAS NEGERI (SMAN) 2 BUKITTINGGI - Rasyidah, Intan Nuraini; Hasnawati, Hasnawati (UIN Imam Bonjol Padang, 2024)
This research is motivated by problem srelated to the Role of thePrincipal as a Leader at State Senior High School 2 Bukittinggi, the Principal has shown empathy by listening to the teacher, but has not listened well, the Principal is too hasty when making decisions. This study uses a qualitative descriptive method with data collection techniques, namely: interview, observation, and documentation methods. Data analysis techniques in this study, namely, with data reduction (data reduction), data display (data presentation), conclusion drawing/verification (drawing conclusions). The results of this study are the role of the principal as a leader in SMA Negeri 2 Bukitiinggi, 1) Having a strong personality such as the empathetic attitude of the principal listening to teacher talks well, paying attention, providing tolerance by not differentiating the teacher interms of position , giving sanctions for those who violate discipline, namely, giving warnings and giving sanctions to teachers who violate school rules, setting good examples and examples, for example, the principal is presenton time and welcomes teachers and students at the gate; 2) Understand theteacher's condition and respect the teacher by listening to the teacher's reasons for being late; 3) Being able to make decisions, the principal includes all teaching staff and educational staff, conducts an evaluation to assess the extent to which decisions have been implemented; 4) communication skills, creating harmonious relationships, the principal says politely and politely when talking to the teacher